2016
DOI: 10.1007/s11187-016-9749-2
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of investment subsidies: evidence from a regression discontinuity design

Abstract: This paper analyzes the effects of an investment subsidy program for small and medium-sized enterprises in Flanders from 2004 to 2009. The subsidies were awarded according to a ranking system that favored young, growing and productive firms with a strong cash flow, granting subsidies to the highest scoring firms until the depletion of funds. The nature of this allocation system creates a sharp cut off in granting the subsidy according to the score, allowing us to estimate the causal impact of the subsidies usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…Our finding is in contrast with previous findings from the agricultural sector (Ratinger et al, 2013), but it supports findings from the meat processing industry (Spicka et al, 2017). Decramer and Vanormelingen (2016) found that the effect of the subsidies on the growth of the receiving firms was rather limited. Only for the very small firms was there a positive effect on investment, employment, sales, value added and productivity.…”
Section: ]supporting
confidence: 57%
See 1 more Smart Citation
“…Our finding is in contrast with previous findings from the agricultural sector (Ratinger et al, 2013), but it supports findings from the meat processing industry (Spicka et al, 2017). Decramer and Vanormelingen (2016) found that the effect of the subsidies on the growth of the receiving firms was rather limited. Only for the very small firms was there a positive effect on investment, employment, sales, value added and productivity.…”
Section: ]supporting
confidence: 57%
“…Moreover, investment support should also focus on creating new jobs and improving the quality of life. However, output should increase more than labour costs (Decramer and Vanormelingen, 2016). The hypothesis is that there is a positive dynamic effect of investment support on labour productivity.…”
Section: Dynamic Effects Of Public Investment Support In the Food Andmentioning
confidence: 99%
“…Entrepreneurship researchers may also employ a difference-in-differences design by assigning treatment and control groups based on a naturally occurring phenomenon, such as a change in public policy (Davidsson and Gordon, 2016). Regression discontinuity designs also compare the effect of an intervention where researchers can distinguish between treatment and control groups based on a naturally occurring cutoff (Decramer and Vanormelingen, 2016).…”
Section: Causal Inference Asmentioning
confidence: 99%
“…To the extent that the fixed costs represent investments in information acquisition, they have a public good aspect and it is better to incur them only once (Copeland 2008 Decramer and Vanormelingen, 2016). At the national level, the Belgian government operates the Delcredere agency, which guarantees export credit and provides default insurance (for an assessment see Abraham and Dewit, 2000).…”
Section: Theoretical Justificationsmentioning
confidence: 99%